2013
DOI: 10.1177/0961203313514125
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of detached podocytes in the Bowman's space as a marker of disease activity in lupus nephritis

Abstract: Podocyte damage is an important pathogenic component of glomerular disease progression. This study is a trial to clarify the value of counting and scoring the number of shed Bowman's space podocytes as an activity parameter of lupus nephritis, a trial that has not been conducted before. This study was performed on 42 female patients with the clinical diagnosis of lupus nephritis. Beside the routine stains tissue sections were stained by colloidal iron and anti podocalyxin for sialomucin. Podocytes in the Bowma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…More recently, several groups have shown that podocytes themselves do migrate to Bowman's capsule following podocyte depletion (9,14,26,27,40,41) mice in the current study to determine whether this phenomenon exists. As expected, at baseline before disease in mice that received doxycycline to induce permanent podocyte labeling, ZsGreen fluorescence was restricted to podocytes in the glomerular tuft, and was not detected along Bowman's capsule.…”
Section: A B Cmentioning
confidence: 81%
“…More recently, several groups have shown that podocytes themselves do migrate to Bowman's capsule following podocyte depletion (9,14,26,27,40,41) mice in the current study to determine whether this phenomenon exists. As expected, at baseline before disease in mice that received doxycycline to induce permanent podocyte labeling, ZsGreen fluorescence was restricted to podocytes in the glomerular tuft, and was not detected along Bowman's capsule.…”
Section: A B Cmentioning
confidence: 81%
“…Renal tubule epithelial cells play an indispensable part in glomerular filtration barrier [ 5 ]. The structural and functional integrity of renal tubule epithelial cells have close relation with the maintenance of glomerular filtration function [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…We had 29 patients with confirmed detachment by routine light and electron microscopy. Their paraffin blocks were searched for any residual glomerular tissue to be stained by a special podocalyxin stain (colloidal iron) [ 16 18 ]. Of the nine patients who were eligible for this revision, the special stain confirmed detached cells in five of them, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To the best of our knowledge, no study has discussed the ability of LM to detect podocyte detachment by routinely used stains. All the available studies discussed podocyte detachment as described with EM or by special stains or by counting all the currently available podocytes within the glomerulus [ 9 , 10 , 16 , 22 ]. We made the hypothesis that if we succeeded in confirming the ability of LM to detect detached podocytes, this would add a new, inexpensive, and easy method for in-depth evaluation of LM sections in patients with apparent MCD.…”
Section: Discussionmentioning
confidence: 99%